MEDB-13. Neurocognitive and radiological follow-up of children under 5 years of age treated for medulloblastoma according to the HIT-SKK protocol. (3rd June 2022) - Merlin, Marie-Sophie; Schmitt, Emmanuelle; Mezloy-Destracque, Malika; Dufour, Christelle; Riffaud, Laurent; Puiseux, Chloé; De Carli, Emilie; Bodet, Damien; Icher, Céline; Doz, François; Faure-Conter, Cécile; Pagnier, Anne; et al.
Abstract: BACKGROUND: HIT-SKK protocol is used for the treatment of low risk medulloblastomas in young children with the aim of eliminating cranial irradiation and its long-term side effects, in particular neuropsychological (NP) sequelae. This therapy includes IV and intraventricular (ITV) methotrexate (MTX) potentially responsible for leukoencephalopathy (LE) and neurocognitive disorders.The objectives are to describe the risk factors and the course of LE, and to investigate its impact on long-term neurocognitive and behavioural outcome. METHODS: A French retrospective, multicenter study including 35 children under 5 years of age, treated between 2009 and 2017, with a median follow up of 72 months. All follow-up MRIs including assessment of the severity of the LE (Fazekas and CTCAE grading) and all NP evaluations were centrally rewieved. RESULTS: 25/34 evaluable patients presented a LE during follow up, in a median delay of 2 months (1 - 17 months) after the start of chemotherapy. Grade 2 and 3 abnormalities were correlated with higher cumulative dose of ITV -MTX (p=0, 01). Full Scale IQ (FSIQ) and Wechsler indexes were in the average or low average of the reference population. FSIQ was deficient in 7/20 evaluable patients. Processing speed (PSI) was the most frequently impaired neurocognitive domain: 9/20 patients with borderline or very low score, all having received a significantly higher cumulative dose of ITV-MTX (p=0, 04). A decrease in overall NP scores was observed in patients for whom grade 2 or 3 LE persisted at the end of follow-up with an average FSIQ estimated at 82.1 (SD 16.9) versus 94.2 (SD 20.6). This decrease was significant for PSI (p=0, 049). LE and neurocognitive impairments were not correlated with a younger age at diagnosis. CONCLUSION: This study confirmed the responsibility of MTX, and in particular ITV-MTX therapy in the onset and, most often, persistence of LE and its association with neurocognitive disorders.